Human Amnion Epithelial Cells and Their Derived Exosomes Alleviate Sepsis-Associated Acute Kidney Injury via Mitigating Endothelial Dysfunction - Chi, Dongxuan; Chen, Ying; Xiang, Chengang; Yao, Weijian; Wang, Hui; Zheng, Xizi; Xu, Damin; Li, Nan; Xie, Min; Wang, Suxia; Liu, Gang; Li, Shuangling; et al. (Frontiers in Medicine, 2022)
Background: Sepsis is characterized by organ dysfunction resulting from a patient’s dysregulated response to infection. Sepsis-associated acute kidney injury (S-AKI) is the most frequent complication contributing to the morbidity and mortality of sepsis. The prevention and treatment of S-AKI remains a significant challenge worldwide. In recent years, human amnion epithelial cells (hAECs) have drawn much attention in regenerative medicine, yet the therapeutic efficiency of hAECs in S-AKI has not been evaluated. Methods: Septic mice were induced by cecal ligation and puncture (CLP) operation. hAECs and their derived exosomes (EXOs) were injected into the mice via tail vein right after the CLP surgery. The 7-day survival rate was observed. Serum creatinine level was measured and HE staining of tissue sections was performed 16 hours after CLP. Transmission electron microscopy was used to examine the renal endothelial integrity in CLP mice. Human umbilical vein endothelial cells (HUVECs) were treated with lipopolysaccharide (LPS) and EXOs. ZO-1 localization was observed by immunofluorescence staining. Expression of p-p65, p65, VCAM-1 and ZO-1 in the kidney was determined by Western blot. Results: hAECs decreased the mortality of CLP mice, ameliorated septic injury in the kidney and improved kidney function. More precisely, hAECs suppressed systemic inflammation and maintained the renal endothelial integrity in septic animals. EXOs from hAECs exhibited similar renal protective effects as their parental cells. EXOs maintained endothelial cell adhesion junction in vitro and inhibited endothelial cell hyperactivation in vivo. Mechanistically, EXOs suppressed pro-inflammatory NF-κB pathway activation in LPS-treated HUVECs and in CLP mice kidneys. Conclusions: Our results indicate that hAECs and their derived exosomes may ameliorate S-AKI via the prevention of endothelial dysfunction in the early stage of sepsis in mice. Stem cell or exosome-based therapy targeting endothelial disorders may be a promising alternative for treatment of S-AKI.